THU0052 The Role of the Proinflammatory Mediator High-Mobility Group Box Protein 1 (HMGB1) in Anti-Collagen-Antibody-Induced Arthritis is Dependent on Vascular Endothelial Growth Factor (VEGF). (9th June 2015) - Biscetti, F.; Flex, A.; Pecorini, G.; Angelini, F.; Arena, V.; Stigliano, E.; Gremese, E.; Tolusso, B.; Ferraccioli, G.
Abstract : Background: High-mobility group box 1 (HMGB1) is a non-histone nuclear protein that is released extracellulary and has been implicated in rheumatoid arthritis (RA) and angiogenesis 1, 2 . Although HMGB1 is abundantly expressed throughout the inflamed synovium, the mechanism by which this protein is involved in the development of RA is still not well known. Objectives: The purpose of the study was to better define the role of HMGB1 in the synovial angiogenesis and pathogenesis of RA. Methods: Balb/c mice were injected with monoclonal anti-collagen antibody cocktail followed by lipopolysaccharide. Animals were evaluated every 3 days after the infusion of the antibody cocktail for arthritis incidence and each paw was evaluated and scored individually on a scale of 0–4, with 4 indicating the most severe inflammation. The arthritis index (AI) that expressed a cumulative score for all paws was calculated for each animal. To investigate the role of HMGB1 in pathological synovial angiogenesis in RA, three groups of mice were studied: mice treated with HMGB1, mice treated with the selective HMGB1 inhibitor BoxA and untreated control mice. To further define and clarify the HMGB1 –VEGF interaction, additional groups of animals were treated with BoxA and with vascular endothelial growth factor (VEGF) inhibitor, the sFlt-1 plasmid. Results: Immunohistochemical and ELISA analyses confirmed over-expression of HMGB1 and VEGF in the areas of the synovium where more inflammation and neoangiogenesis were present. Interestingly, the selective blockade of HMGB1 or of VEGF alternatively resulted in a lower severity of arthritis evaluated by AI ( p =0.003 and p =0.001) (Figure 1 ). Furthermore, exogenous HMGB1 administration caused a worsening of arthritis, associated with VEGF up-regulation and increased synovial angiogenesis. Surprisingly, the selective inhibition of VEGF resulted in the lack of induction of arthritis also in mice receiving exogenous HMGB1 ( p <0.001). ELISA analyses performed on peripheral blood and synovial fluid demonstrated a significant reduction of IL-1β ( p <0.001), IL-6 ( p <0.001) and TNF-α ( p <0.001) in mice where HMGB1 and VEGF pathways were blocked. Interestingly, the selective blockade of HMGB1 and VEGF resulted in an increase of the peripheral IL-17A concentration ( p <0.001). Conclusions: The development of arthritis mediated by HMGB1 and the synovial angiogenesis can be blocked by inhibiting the VEGF activity. The pro-inflammatory and pro-angiogenic cytokine IL-17A is increased when HMGB1 is inhibited, but the synovial angiogenesis is nevertheless reduced in this model of arthritis. These data confirm that the blood vessels neoformation at the synovial level is dependent on VEGF. Taken together, these findings shed new light on the role of this nuclear protein in the pathogenesis of arthritis in an RA-like model. References: Park SY et al. HMGB1 induces angiogenesis in rheumatoid arthritis via HIF-1α activation. Eur J Immunol. 2014 Dec 24. Yang S et al. High-mobility group box-1 and its role in angiogenesis. J Leukoc Biol. 2014 Apr;95(4):563-74. Acknowledgements: The authors acknowledge the contribution of Prof. Kensuke Egashira, from the Department of Cardiovascular Medicine, Kyushu University, Fukuoka, Japan. Disclosure of Interest: None declared